FACILITE LA PRODUCTION ORALE EN CLASSE DE LANGUE EN MILIEU PLURILINGUE A TRAVERS DES SCENES MUETTES - Agbessime, Komla Enyuiamedi (European Scientific Journal, ESJ, 2014)
In an action-oriented and communicative approach, this methodology takes into account the oral aspect of language teaching in multilingual environment. It evokes a set of proposals on learning skills that trigger linguistic practice and the methodological and pedagogical perspectives, modern and innovative that can be put into action in a language teaching class. This class offers broadly practical mimed sequences. It is in fact representations of meanings by a silent scene played for the caller in a cognitive approach to analyze through the intervention of consciousness for understanding and acquisition of knowledge in order to necessarily mean something or meet the requirements.